WHO-Aligned Food Safety Knowledge and Misconceptions Among Vocational Food-Processing Students - Kurnia, Nova; Sumarlin, Muhamad; Barrios, Rubilyn G.; de Jesus, Mateus Maia (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
Food safety knowledge is essential for vocational students who handle food during school-based processing activities. This study assessed food safety knowledge and examined selected misconceptions among Grade XI students enrolled in an Agricultural Product Processing Agribusiness program at one public vocational secondary school in West Lombok Regency, Indonesia. A descriptive cross-sectional design with an embedded qualitative explanatory component was used. Of 46 students in the cohort, 10 participated in questionnaire pilot testing and were excluded from the main study. The remaining 36 students completed an 11-item True/False questionnaire aligned with the WHO Five Keys to Safer Food framework and participated in individual semi-structured interviews. Students demonstrated strong recognition of handwashing, kitchen-surface cleanliness, separation of raw and cooked foods during storage, and washing fruits and vegetables. However, misconceptions concerned shared cutting boards, thorough reheating, cooking temperature, prolonged room-temperature storage, and judging water safety by appearance. The mean knowledge score was 7.86 of 11, and the questionnaire showed marginal-to-moderate internal consistency for preliminary group-level diagnostic use (KR-20 = 0.69). Interview findings indicated that some students considered previous cooking sufficient, associated reheating with burning, viewed freshly slaughtered meat as containing few bacteria, and treated clear water as safe. These findings identify curriculum priorities related to cross-contamination, time–temperature control, reheating, and invisible microbiological and chemical hazards. Because the study involved one vocational cohort, the findings should be interpreted as a local diagnostic profile.